5p-3=5(8p+6)-4(-5+9p)

Simple and best practice solution for 5p-3=5(8p+6)-4(-5+9p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-3=5(8p+6)-4(-5+9p) equation:


Simplifying
5p + -3 = 5(8p + 6) + -4(-5 + 9p)

Reorder the terms:
-3 + 5p = 5(8p + 6) + -4(-5 + 9p)

Reorder the terms:
-3 + 5p = 5(6 + 8p) + -4(-5 + 9p)
-3 + 5p = (6 * 5 + 8p * 5) + -4(-5 + 9p)
-3 + 5p = (30 + 40p) + -4(-5 + 9p)
-3 + 5p = 30 + 40p + (-5 * -4 + 9p * -4)
-3 + 5p = 30 + 40p + (20 + -36p)

Reorder the terms:
-3 + 5p = 30 + 20 + 40p + -36p

Combine like terms: 30 + 20 = 50
-3 + 5p = 50 + 40p + -36p

Combine like terms: 40p + -36p = 4p
-3 + 5p = 50 + 4p

Solving
-3 + 5p = 50 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
-3 + 5p + -4p = 50 + 4p + -4p

Combine like terms: 5p + -4p = 1p
-3 + 1p = 50 + 4p + -4p

Combine like terms: 4p + -4p = 0
-3 + 1p = 50 + 0
-3 + 1p = 50

Add '3' to each side of the equation.
-3 + 3 + 1p = 50 + 3

Combine like terms: -3 + 3 = 0
0 + 1p = 50 + 3
1p = 50 + 3

Combine like terms: 50 + 3 = 53
1p = 53

Divide each side by '1'.
p = 53

Simplifying
p = 53

See similar equations:

| x^2-4x+1=10 | | 2x=18*5 | | m-51=-70 | | -112+x=40-7x | | 27m^2=3 | | 2-2-4= | | 1.5y=2.3 | | 4(x-y)+z=2x+z | | -2(x+2)-2x=5x-9 | | 3d=7*21 | | (x^2+4x-6)(x^2+6x-3)= | | 112+x=40-7x | | 0.5(3g-2)=g | | 3x+4y=35 | | d+25=b | | -3h+12-4h=-7h-16 | | -1=(x/4)-3 | | 2(-8+8x)+5x=-100 | | 3x+49=3 | | 3x+3y=20 | | 8c=7*16 | | 3x+2+2x=x+16 | | 2a+3a+4=5a-18 | | x-1=2x-2 | | 315=-5(1-8v) | | 3t-t=-22 | | 458=6x+308 | | -8(-2x-5)-4x=88 | | -34=-4(x+4)-5x | | y=(8-6k)x | | 3y-9x=21 | | 3a=2*12 |

Equations solver categories